Changing translation practices and moving boundaries in translation studies - Gambier Yves; Kasperẹ Ramunė (JOHN BENJAMINS PUBLISHING CO, 2025)
This article aims at describing the changes in translation by referring to practices such as localization, amateur translation, translating in the media. The changes are enhanced by the computing, information, and communication technologies. In three decades, a new work environment has shaken up the translator's world. New types of translators are emerging, with a new hierarchy between them, in parallel with a multiplication of labels created for "translation." The concept of translation has, therefore, become ambiguous and, relating to it, other concepts, such as text, need to be revisited.